Multiple Long-Term Conditions and Disability are Independently Associated with Higher Risk of Fall Among Community Adults: A Cross-Sectional Study [Letter] - Wang R; Yao L (Dove Medical Press, 2024)
Rong Wang,1 Li Yao2 1School of Nursing, Ningxia Medical University, Yinchuan, Ningxia, 750004, People’s Republic of China; 2Department of Cardiovascular Medicine, General Hospital of Ningxia Medical University, Yinchuan, Ningxia, 750004, People’s Republic of ChinaCorrespondence: Li Yao, Department of Cardiovascular Medicine, General Hospital of Ningxia Medical University, Yinchuan, Ningxia, 750004, People’s Republic of China, Email 13995088029@163.com